A new method to disperse CdS quantum dot-sensitized TiO(2) nanotube arrays into P3HT:PCBM layer for the improvement of efficiency of inverted polymer solar cells - Li, Fumin (Springer, 2014)
We report that the efficiency of ITO/nc-TiO(2)/P3HT:PCBM/MoO(3)/Ag inverted polymer solar cells (PSCs) can be improved by dispersing CdS quantum dot (QD)-sensitized TiO(2) nanotube arrays (TNTs) in poly (3-hexylthiophene) and [6,6]-phenyl-C(61)-butyric acid methyl ester (P3HT:PCBM) layer. The CdS QDs are deposited on the TNTs by a chemical bath deposition method. The experimental results show that the CdS QD-sensitized TNTs (CdS/TNTs) do not only increase the light absorption of the P3HT:PCBM layer but also reduce the charge recombination in the P3HT:PCBM layer. The dependence of device performances on cycles of CdS deposition on the TNTs was investigated. A high power conversion efficiency (PCE) of 3.52% was achieved for the inverted PSCs with 20 cyclic depositions of CdS on TNTs, which showed a 34% increase compared to the ITO/nc-TiO(2)/P3HT:PCBM/MoO(3)/Ag device without the CdS/TNTs. The improved efficiency is attributed to the improved light absorbance and the reduced charge recombination in the active layer.